Dhamma principles of honesty for the development of Thai society - Thammapalo, Phrakrubaidika Suthat (Journal of Thammawat, 2020)
Problems in Thai society today are increasing. And resulting in Buddhism being affected and overlooked Because people are obsessed with adopting Western values Development focuses on bringing new technology instead, such as using machinery instead of human labor. There is a competition between us. And at the same time destroying the natural environment, such as physical environment such as soil, water, air, forest, upstream, atmosphere, and social environment is the attitude, values, ethics and culture of these values ​​are the problems that occur today. Which is a big problem that cannot be solved because most of the problems are fixed at the end of the cause From history and the importance of the word Such "honesty" is an important variable that makes the author interested to study and analyze. This work will select only the "honesty" issues because King Prajadhipok’s Institute studies and research issues. "Honesty" but no academic is interested. And focus on the study of "honesty". Therefore, this work is interested to study in terms of meaning, type, value and importance. Dharma that supports honesty and ways to develop honesty in the mind and society Which will benefit the development of the integrity of the citizens from kindergarten to university Including politicians Government officials and the private sector in relation to work in order to facilitate social development and the nation to be more transparent